PENGARUH MODEL PEMBELAJARAN STAD DAN NHT TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Sri Rahayu (Universitas PGRI Adi Buana Surabaya, 2015)
This research was motivated by a change of the curriculum from the curriculum KTSP is changed into the 2013curriculum which aims to make the 2013 curriculum students productive, innovative and effective. In order for a teacher-centered learning into an interactive learning. Therefore, the necessary learning model that can support the passage of the curriculum in 2013 that STAD cooperative learning model and cooperative learning model NHT. Formulation of the problem in this research is